(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: To the best of our knowledge, no study has yet reported on biorhythms of Threshold Exposure Duration for Recognition of Test Objects (TEDRTO). Purpose: To investigate biorhythms of TEDRTO over a school day in children learning under intensive visual load conditions. Materials and Methods: Ninety eight ophthalmologically healthy children (aged 13 to 17 years) attending a boarding school with advanced learning of a number of subjects underwent examination. A special electronic apparatus was used to present a test object (a Landolt’s ring having an angular size of 8 minutes of arc) to the child. Binocular TEDRTO measurements were performed at five time points during the day: at 8 o’clock AM, 11 o’clock AM, 2 o’clock PM, 4 o’clock PM, and 8 o’clock PM). Results: Friedman’s non-parametric test demonstrated that TEDRTO values gradually and statistically significantly increased (?? = 52.4; р=0.00000) during a school day. In addition, the number of children with TEDRTO values greater than 1 ms at various times of measurement gradually increased during a school day, and these children usually complained of increased visual fatigue. Conclusions: There was a statistically significant worsening in TEDRTO values in schoolchildren learning over a day under intensive visual load conditions.